Auditory Attention: Time of Day and Type of School - Picolini, Mirela Machado; Stivanin, Damiane; Sampaio, Ariane Risatto; Salvador, Karina Krahembuhl; Lauris, José Roberto Pereira; Feniman, Mariza Ribeiro (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The sustained auditory attention is crucial for the development of some communication skills and learning.Objective: To evaluate the effect of time of day and type of school attended by children in their ability to sustained auditory attention.Method: We performed a prospective study of 50 volunteer children of both sexes, aged 7 years, with normal hearing, no learning or behavioral problems and no complaints of attention. These participants underwent Ability Test of Sustained Auditory Attention (SAAAT). The performance was evaluated by total score and the decrease of vigilance. Statistical analysis was used to analysis of variance (ANOVA) with significance level of 5% (p ≤ 0.05).Results: The result set by the normative test for the age group evaluated showed a statistically significant difference for the errors of inattention (p = 0.041, p = 0.027) and total error score (p = 0.033, p = 0.024), in different periods assessment and school types, respectively.Conclusion: Children evaluated in the afternoon and the children studying in public schools had a poorer performance on auditory attention sustained.
Keywords: attention; hearing; child; rating